Case Studies: Person-Centered Health Coaching in People With Negative Social Determinants of Health - Susan Butterworth, PhD; Stacia Potempa, MSN, RN; Candia Laughlin, MS, RN; Marna Flaherty-Robb, MSN, RN; Margaret Calarco, PhD, RN; Karen Harden, DNP, RN; Patricia Schmidt, MS, RN; Philip Furspan, PhD; Kathleen Potempa, PhD, RN (Elsevier, 2023)
Social determinants of health are the conditions in the environment that influence health outcomes, such as housing, transportation, and neighborhoods. In this report, we examine 3 cases of participants with social risk factors who participated in a health coaching intervention study. The study was a science-based, nurse health coaching model provided to older adult participants in a Midwestern state designed to equip and empower them to achieve and maintain their health and optimum function to support independent living at home. The program was an 8-week virtual coaching method using weekly, 30-minute, 2-way video coaching sessions with participants. For each of the 3 cases, we describe the patterns of engagement, early and later health goals as coaching progressed, and the types of outcomes achieved. From these case studies, we illustrate how social determinants may affect the types of goals, processes, and potential outcomes achieved by participants of health coaching programs. From these insights, we propose directions in health policy and services and future research considerations.